Novel cement curing technique by using controlled release of carbon dioxide coupled with nanosilica - Jassam, Taha M.; Kien-Woh, Kow; ng yang-zhi, Jason; Lau, Bonnie; Yaseer, M.M.M. (Elsevier, 2019)
Nanotechnology has attracted a lot of interest in the modification of building materials involving nanoparticles. Among the nanoparticles available, the incorporation of nano-silica draws intense attention due to the similarity of its chemical composition with cement and its pozzolanic properties. In this work, the potential capability to utilise CO2 in improving cement composites properties through carbonation acceleration mechanism was explored. In this study, various type of nano silica was used as a CO2 carrier and incorporated into cement mortar design with different amount of carbonated silica loading, ranging from 0.55 wt% to 2.42 wt% and cured in water and ambient air condition. The aim of this study is to examine the effects on the compressive strength of nano-silica impregnated with CO2 and incorporated into cement mortar. From the results, it was found that at 1.89% silica loading, the hydrophilic silica mortar (HSAM) samples can achieve the highest compressive strength of 34.1 MPa at 7 days and 40.7 MPa at 28 days, with a percentage gain of +38.06% and +17.29% respectively as compared to blank samples. However, the incorporation of silica for more than 1.89 wt% resulted in a negative effect on the compressive strength gain of HSAM samples. By the incorporation of 2.42 wt%, the samples showed a significant drop in compressive strength of −21.46% at 7 days and −17.29% at 28 days. The results proved that nano-silica coupled with CO2 can accelerate curing of cement mortar by means of carbonation.